ESTRUTURA DA COMUNIDADE E REDES TRÓFICAS DE ABELHAS E VESPAS SOLITÁRIAS (HYMENOPTERA: ACULEATA) EM ÁREAS DE MATA ATLÂNTICA E DE CULTIVOS - Iantas, Jucélia (2013)
Bees and wasps (Hymenoptera: Aculeata) stand out as important functional groups for the service rendered at terrestrial ecosystems. Due to the threats human actions can have on biodiversity, species composition and patterns of trophic networks communities have been related to changes in habitat structure. This paper proposes a general study on the community structure and interactions networks structure of solitary bees and wasps that nest in pre-existing cavities and respective parasitoids. This study was conducted in the municipalities of Porto União (SC) and União da Vitória (PR) between August/2011 and July/2012 in environments fragments of forest and cultivated areas. Sampling for these insects were used trap nests of wood with different diameters and grouped in blocks. In the field each block was fixed on a stake of 1.5 m above the ground. Traps were inspected biweekly, and each occupied nest was removed and replaced by another of the same diameter. We sampled 846 nests of 12 species of wasps, six of bees and 16 species of parasitoids. Most was established by wasps nests (91.5%) and the remainder (8.5%) by bees. The most abundant species of wasps were Trypoxylon opacum (n = 321) and Pachodynerus guadulpensis (n = 148). Among the bees, Centris tarsata (n = 43) and Epanthidium autumnale (n = 18). Regarding the environment, the forest presented 11 species, six exclusive. Areas of grape cultivation also totaled 11 species, with three unique. The lowest number of species recorded in the areas of strawberry (S = 9) with only a exclusive kind. The greatest similarity between the composition and abundance of species was found among environments grape and strawberry crops (P = 0.666). The grape growing environment presented a nested pattern of interaction. It was also the environment with the highest number of interactions and parasitoid species. In all environments connectance values indicate more general networks. Recording to the diversity standardized index (H`2), the network for the forest environment was the most expert.